Morpho-physiological Changes of Rotated Barley and Faba bean plants in Response to Nickel Toxicity and Chemical and Biological Fertilization - Sajad Shaker Kouhi (University of Tabriz, 2021)
Abstract Background and Objective: The objective of this research was to assess the effect of nickel (Ni) toxicity on rotated barley and faba bean characteristics under chemical and biological nitrogenous fertilizers.   Materials and Methods: A greenhouse experiment with factorial arrangement based on randomized complete block design with three replications was conducted in two years of 2016-2017 at the Faculty of Agriculture, University of Tabriz. In the first part, barley seeds were sown using 36 pots with Ni levels of 0, 10, 100 and 200 mg.kg-1 and nitrogen (N) fertilizer (control, urea and Nitroxin). In the second part, faba bean seeds were cultivated in 72 pots. In this part, the crop rotation factor was applied in addition to N fertilizer and Ni treatments.   Results: The results indicated that increasing Ni levels in soil markedly decreased plant height, leaf water content, chlorophyll content index, and root and shoot dry matters, but increased electrolyte leakage of barley and faba bean plants. The high level of Ni (100 and 200 mg.kg-1) was led to soil toxicity. While, the low nickel concentration (10 mg.kg-1) improved the growth of plants.   Conclusion: It can be concluded that application of N fertilizer improved the growth conditions of plants under Ni stress. Cultivation of barley significantly decreased Ni toxicity in the soil, leading to an improvement in faba bean performance in rotation.